The best laid plans : a novel - Sheldon, Sidney (New York : William Morrow, 1997)
"The Best Laid Plans tells the explosive story of the beautiful and ambitious Leslie Stewart, who learns that for some men power is the greatest aphrodisiac, and of Oliver Russell, the handsome governor of a small southern state, who finds out why hell has no fury like a woman scorned."--BOOK JACKET. "With the unexpected twists and turns that are the hallmarks of his novels, Sidney Sheldon spins a tale of two equally determined people headed on a collision course. Oliver has a strategy to win the White House; Leslie has a scheme to make him wish he'd never been born. They both should have known that even the best-laid plans can go dangerously astray...with deadly consequences."--BOOK JACKET. "The Best Laid Plans takes readers inside two of America's most powerful and ruthless institutions: the world of politics with its scandals, corruption, and cover-ups; and that of newspaper publishing, where it is not unusual to use the power of the press to destroy lives - or bring down heads of state - in pursuit of a story or to settle a score."--BOOK JACKET.
Keywords: Newspaper publishing -- Kentucky -- Fiction; Governors -- Kentucky -- Fiction; Political corruption -- Fiction; Political fiction